Usulan Rancangan Tata Letak Fasilitas Produksi di PT NS Bluescope Lysaght Indonesia - Ivena Faustina; Teguh Oktiarso; Yurida Ekawati (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
This study addresses the changes in production layout at PT NS Bluescope Lysaght Indonesia, caused by the relocation of the factory to a wider land and the use of a different crane. The new factory utilizes Gantry Crane that uses rails on the production floor, which limits the land used. The study uses the Computerized Relationship Layout Planning (Corerap) algorithm to propose alternative production layouts. Four layout proposals were generated, and the layout proposal with the smallest product transfer distance was selected. The results showed that layout proposal 4 was the most effective and efficient, with a total displacement range of 453.7 meters. This study highlights the importance of using advanced algorithms to optimize production layouts, particularly when changes in equipment and facilities occur. The proposed layout can potentially increase productivity and efficiency in production. The study contributes to the body of knowledge on production layout planning and optimization using computerized algorithms.